2014
DOI: 10.1093/cvr/cvu146
|View full text |Cite
|
Sign up to set email alerts
|

RIP3, a kinase promoting necroptotic cell death, mediates adverse remodelling after myocardial infarction

Abstract: Here, we show that RIP3-dependent necroptosis modulates post-ischaemic adverse remodelling in a mouse model of MI. This novel signalling pathway may thus be an attractive target for future therapies that aim to limit the adverse consequences of myocardial ischaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
240
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(269 citation statements)
references
References 35 publications
14
240
0
1
Order By: Relevance
“…4C). Meanwhile, when compared to I/R alone, the addition of Z‐VAD alone in I/R rats did not affect the expression of RIP3, which is the key kinase in promoting necroptotic cell death 36. Accordingly, it could be speculated that the necroptotic epithelial cell death is likely to account for the mucosal injury after caspase inhibition.…”
Section: Discussionmentioning
confidence: 98%
“…4C). Meanwhile, when compared to I/R alone, the addition of Z‐VAD alone in I/R rats did not affect the expression of RIP3, which is the key kinase in promoting necroptotic cell death 36. Accordingly, it could be speculated that the necroptotic epithelial cell death is likely to account for the mucosal injury after caspase inhibition.…”
Section: Discussionmentioning
confidence: 98%
“…In a study using an in vivo model of myocardial infarction 24 hours after permanent ligation of the left anterior descending coronary artery, overexpression of RIPК3 was detected via an immunoblot test in mouse hearts (10). In that study, RIPК3-deficient mice had a significantly better ejection fraction and less hypertrophy in magnetic resonance imaging (MRI) studies 30 days after experimental infarction in comparison to wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to apoptosis, this process is tightly regulated by distinct molecules and has morphological features of both necrosis and inflammation (3,(6)(7)(8)(9). Nevertheless, the exact pathways activating this programmed necrosis are not fully understood (10). A study has shown that tumor necrosis factor alpha (TNF-α) is a factor that triggers the formation of a complex, called necrosome, in the cytoplasm between receptor-interacting protein kinase 1 (RIPK1) and receptor-interacting protein kinase 3 (RIPK3) (7).…”
Section: Introductionmentioning
confidence: 99%
“…RIP3 co‐localized with mitochondria when necrosis was induced in a kinase activity‐dependent manner and promoted mitochondrial metabolism and ROS production by activating the PYGL, GLUL and GLUD1, leading to the consequent necrosis as mentioned above (Figures 3 and 4). 60 In a recent study, Ting Zhang et al found that siRNA‐mediated knockdown of Cypd markedly alleviated RIP3‐induced cardiomyocyte necrosis as assessed by cellular ATP content and LDH release, further revealing the close relationship between these 2 pathways 61…”
Section: Signalling Interactionmentioning
confidence: 98%
“…As necrosis can be induced by the activation of the death receptors, it is not surprised that RIP1/RIP3‐mediated death receptor pathway contributes to the necrosis of cardiomyocytes in heart failure patients. In the permanent myocardial ischaemia animal model, RIP3 knockout would decrease the inflammatory response and hypertrophic growth of the cells while the ejection fraction was increased 60. It had been also observed that the markers of necrosis, phospho‐MLKL, are also up regulated in the end‐stage heart failure patients 71.…”
Section: Necrosis In Heart Diseasesmentioning
confidence: 99%